Atlanto-axial Joint Distraction in the Treatment of Select Cases of Basilar Invagination, Syringomyelia and Fixed Atlanto-axial Dislocation - Goel, Atul (Nepal Journal of Neuroscience, 2005)
Not available. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, page: 1-6